Experienced economic approach in tourism product development in The Keranggan Tourism Village, South Tangerang - Juliana Juliana; Sabrina Oktaria Sihombing; Ferdi Antonio (Jurnal Pariwisata Pesona, 2022)
The experience economy approach shows that consumers are not only offered a product as a commodity but as an experience. Experience in a destination will distinguish one place from another. The purpose of this research is to examine the four categories of experiences owned by the Keranggan Tourism Village and to provide a product development strategy based on that experience. The four categories are aesthetic experience, entertainment, education, and getting out of the routine. Kampung Keranggan has been developed since 2012 and already has several tourist attractions that are visited by tourists. The research method used is descriptive qualitative. Data collection was done by interviewing the Tourism Awareness Group and field observations. The findings of this study are that Kampung Keranggan already has aspects in realizing the experience, but the packaging still needs to be developed. Among them, the educational experience for tourists is given the experience of food processing production, from harvesting cassava, peeling, steaming, and mashing to forming opaque chips. The results of this experience study will be included in the tourism product development strategy.